Special power relationship as soon as the muscles of the abdomen and the explosive power of the two men the completion of some activities of track and field games for girls - Baez, Rabaz (Journal of Physical Education, 2010)
A good preparation cause of a good result and the is by preparation of play the players & develop them for complete this obligation & to reamer a good physical preparation with preparation of training for power speed for students by scientific method & help to gain dew dope physical power & to gain the best result in the playing of track & field. Most The process of training of power & speed have good & properly and this is has relation with physical characteristics to gain these results & relation ships with other parts of physical fitness principles. The important of this research that the static practice of the student by wide & vary contains these practices; (running, jumping & throwing) & to executive these practices to a model style & should this student can has a high degrees in speed & power of muscular and the important of dividing this effort possibly to game these activities in the time of the track and field: lessons. the aim of a research know the relation ship between power signified by speed of abdominal muscles & power explosive for legs to gain some practices of track and field and researcher used the descriptive program to appropriate with research and its results . & choose the sample of the research by haphazard way of the girl students of the College of Physical education in the koya university first step the consists of (15) students & far away two girl students because they were players of selected an activates and the sample of the research remains (13) girl students and (%77.77) in the original society of the research for the year study of (2009- 2010) The conclusion of the researcher consists of:- 1- Have relation ship between moral correlation & power signified by speed of abdominal muscles & the result levels of activities (running100m Shot put & high jump) for the sample of the research. 2- Have a moral relation ship between the explosive of legs and the result levels of high jump in the sample of the research. 3- Haven't a moral relation ship between explosive power of two legs & the level of result to running 100m for the sample of the research.